Political Economy of COVID-19 on Agriculture & Food Policies: Situating Global Trends - Resnick, Danielle (2020)
Danielle Resnick POLICY SEMINAR Virtual Event - The political economy of COVID-19: Impacts on agriculture and food policies OCT 22, 2020 - 08:30 AM TO 10:00 AM EDT